A Survey of Price Elasticities - Hirsch, W. Z. (Review of Economic Studies, 1951)
A Survey of Price Elasticities Get access W. Z. Hirsch W. Z. Hirsch Jerusalem Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 19, Issue 1, 1950, Pages 50–60, https://doi.org/10.2307/2296271 Published: 01 December 1950